A homozygous nonsense variant in IFT52 is associated with a human skeletal ciliopathy. Issue 6 (15th March 2016) - Girisha, K. M.; Shukla, A.; Trujillano, D.; Bhavani, G. S.; Hebbar, M.; Kadavigere, R.; Rolfs, A.
Abstract : Intraflagellar transport (IFT) is vital for the functioning of primary cilia. Defects in several components of IFT complexes cause a spectrum of ciliopathies with variable involvement of skeleton, brain, eyes, ectoderm and kidneys. We examined a child from a consanguineous family who had short stature, narrow thorax, short hands and feet, postaxial polydactyly of hands, pigmentary retinopathy, small teeth and skeletal dysplasia. The clinical phenotype of the child shows significant overlap with cranioectodermal dysplasia type I (Sensenbrenner syndrome). Whole‐exome sequencing revealed a homozygous nonsense variant p.R142* in IFT52 encoding an IFT‐B core complex protein as the probable cause of her condition. This is the first report of a human disease associated with IFT52 .